3D bioprinted mesenchymal stromal cells in skin wound repair - Luo, Yuansen; Xu, Xuefeng; Ye, Zhiming; Xu, Qikun; Li, Jin; Liu, Ning; Du, Yongjun (Frontiers in Surgery, 2022)
Skin tissue regeneration and repair is a complex process involving multiple cell types, and current therapies are limited to promoting skin wound healing. Mesenchymal stromal cells (MSCs) have been proved could enhance skin tissue repair through their multi-differentiation and paracrine effect. However, there are still difficulties, such as the limited proliferative potential and the biological processes that need to be strengthened for MSCs in wound healing. Recently, three-dimensional (3D) bioprinting is a promising technology for tissue regeneration. 3D bioprinted MSCs could maintain a better cell ability for proliferation and expression of biological factors to promote skin wound healing. It’s reported that 3D bioprinted MSCs could enhance skin tissue repair through anti-inflammatory, cell proliferation and migration, angiogenesis, and extracellular matrix (ECM) remodeling. In this review, we will discuss the progress on the effect of MSCs and 3D bioprinting on the treatment of skin tissue regeneration, as well as the perspective and limitations of current research.